Beyond Ainu studies : changing academic and public perspectives (University of Hawai'i Press, 2014)
In 2008, 140 years after it had annexed Ainu lands, the Japanese government finally recognised Ainu as an Indigenous people. In this moment of political change, it was Uzawa Kanako, an Ainu activist, who signalled the necessity of moving beyond the historical legacy of 'Ainu studies'. This volume re-addresses the role of academic scholarship in Ainu social, cultural, and political affairs. Placing Ainu firmly into current debates over Indigeneity, it provides a critical overview of the history and current status of Ainu research.